Biphenotypic Sinonasal Sarcoma—Case Report and Review of Clinicopathological Features and Diagnostic Modalities - Chitguppi, Chandala; Koszewski, Ian; Collura, Kaitlin; Curtis, Mark; Nyquist, Gurston; Rabinowitz, Mindy; Rosen, Marc (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Biphenotypic sinonasal sarcoma is a recently described malignancy showing dual differentiation with both myogenic and neural elements. Due to its histologic similarities to other sinonasal malignancies, it is a diagnostic challenge.Objective The main purpose of this article is to report a case of biphenotypic sinonasal sarcoma and to consolidate data and provide a comprehensive review regarding pathological differences between biphenotypic sarcoma and other sinonasal malignancies and diagnostic modalities used for biphenotypic sarcoma.Material and Methods A systematic review of all cases of biphenotypic sinonasal sarcoma was performed using electronic databases (PubMed and Medline). Data collected included age, gender, symptoms, sub-site of origin, immunophenotyping, metastasis, recurrence, treatment, duration of follow-up, and survival outcomes.Results Ninety-five cases of biphenotypic sarcoma were found with mean age at diagnosis of 52.36 years (range, 24–87 years). Female to male ratio was 2.27:1. Extra-sinonasal extension was present in 28%. Immunophenotyping revealed that S-100 and SMA (smooth muscle actin) were consistently positive, while SOX-10 was consistently negative. PAX3-MAML3 fusion [t (2; 4) (q35; q31.1)] was the most common genetic rearrangement. Surgical excision with or without adjuvant radiotherapy was the most frequent treatment modality used. Recurrence was observed in 32% of cases with follow-up. None of the cases reported metastasis. Three patients had died at the time of publication that included one case with intracranial extension.Conclusion Biphenotypic sarcoma is distinct sinonasal malignancy with unique clinicopathological features. Testing involving a battery of myogenic and neural immunomarkers is essential for diagnostic confirmation and is a clinically useful endeavor when clinical suspicion is high.
Keywords: sarcoma; sinus; nasal; biphenotypic; spindle cell